STRATEGI KPU DALAM MENINGKATKAN PARTISIPASI PEMILIH PADA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA SAMARINDA TAHUN 2015 - Dwi Haryono (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
The purpose of this study was to determine the KPU Strategies to Improve Voter participation on Election of Mayor and Deputy Mayor of Samarinda in 2015. Qualitative research methods used, techniques of data collection is done by the research library (library search) and field (Field work search), observation, interviews and documentation. Source of research data with the primary data is purposive sampling technique (key-informant) and snowball sampling (informant) and secondary data. Data analysis technique used is descriptive qualitative data analysis method of Milles and Huberman is condensation, data presentation, conclusions and verification. Conclusions from the study showed a picture that basically strategy commission to enhance participation of voters on election of Mayor and Deputy Mayor of Samarinda in 2015 are strategy institutional strengthening, strategies political socialization, beginner voter education strategy.Keyword: Strategy, Commission, Voter Participation, Election Unison